Ionizing radiation manifesting DNA damage response in plants: An overview of DNA damage signaling and repair mechanisms in plants. (January 2019) - Kim, Jin-Hong; Ryu, Tae Ho; Lee, Seung Sik; Lee, Sungbeom; Chung, Byung Yeoup
Highlights: Update on DNA damage response (DDR) signaling pathways in plants. Recent advances in cellular and phenotypic DDRs, especially induced by IR. Epigenetic regulation of DDRs associated with genome instability in plants. Genotoxic agents and their DDRs in plants. Abstract: Plants orchestrate various DNA damage responses (DDRs) to overcome the deleterious impacts of genotoxic agents on genetic materials. Ionizing radiation (IR) is widely used as a potent genotoxic agent in plant DDR research as well as plant breeding and quarantine services for commercial uses. This review aimed to highlight the recent advances in cellular and phenotypic DDRs, especially those induced by IR. Various physicochemical genotoxic agents damage DNA directly or indirectly by inhibiting DNA replication. Among them, IR-induced DDRs are considerably more complicated. Many aspects of such DDRs and their initial transcriptomes are closely related to oxidative stress response. Although many key components of DDR signaling have been characterized in plants, DDRs in plant cells are not understood in detail to allow comparison with those in yeast and mammalian cells. Recent studies have revealed plant DDR signaling pathways including the key regulator SOG1. The SOG1 and its upstream key components ATM and ATR could be functionally characterized by analyzing their knockout DDR phenotypes after exposure to IR. Considering the potent genotoxicity of IR and its various DDR phenotypes, IR-induced DDR studies should help to establish an integrated model for plant DDR signaling pathways by revealing the unknown key components of various DDRs in plants.